Culture and the ownership concentration of public corporations around the world - Holderness, Clifford G. (Journal of Corporate Finance, 2017)
As a country's attitude toward egalitarianism increases, which means a societal preference for the equal as opposed to hierarchical treatment of individuals, the ownership of the public corporations in the country becomes more concentrated. This finding is robust to a wide range of specifications and methodologies. Once egalitarianism is accounted for, there is no evidence that other cultural attitudes, including trust and religion, or legal protections for public market investors, including those laws that figure prominently in the literature, are related to ownership concentration. One explanation for the robust association between egalitarianism and ownership concentration is that large shareholders are valuable when employees have strong legal rights.